Wind turbine wake: a disturbance to wind resource in wind farms. (1st January 2012) - Aubrun, Sandrine
The present paper aims to summarise the activities from the Laboratory PRISME of the University of Orléans in the context of wind resource assessment with the '3%-vision' suggested by the European Wind Energy Technology Platform, and particularly of the wind turbine wake properties. Based on experimental investigations in an atmospheric boundary layer wind tunnel, some information about the diffusion process of the wind turbine far-wake, the minimal degree of modelling of the rotor to study its far-wake, the unsteady behaviour of the wake and the production loss due to wake effects are presented and discussed.